Unraveling activity of crucial domain HABD protein in dengue virus: Unraveling activity of crucial domain HABD in DENV - Patel, Ayyub; El-Gamal, Basiouny; Abd Ellatif, Mohamed; Alothaid, Hani; Mirdad, Tarek M.; Almalki, Waleed Hassan; Alwabli, Afaf S (Cellular and Molecular Biology, 2022)
Dengue virus (DENV) causes dengue, which is a very common mosquito-borne viral disease. The global incidence of dengue has increased dramatically in recent decades. About half of the world’s population is now at risk. This virus is widespread throughout the tropics, which are influenced by rainfall, temperature, and humidity; however, severe dengue has a higher risk of death when not managed timely. To describe Dengue virus helicase ATP binding domain (HABD) protein in biochemically characterized. Sequences analysis, structure modeling, secondary structure prediction, ATPase assay, unwinding assay, RNA binding assay. HABD has RNA-dependent ATPase and helicase activity which are crucial proteins that participate in the unwinding of double-stranded DNA or RNA by utilizing ATP. RNA binding proteins and DEAD-box RNA helicases have been revealed to contribute to viral replication. Moreover, DEAD-box RNA helicases have been demonstrated to be involved in several features of cellular metabolism of RNA, for example, transcription, splicing, biogenesis, ribosomal processing of RNA, etc. In the present study, we have mainly focused on the Dengue virus’s helicase ATP binding domain (HABD) and observed that HABD contains RNA-dependent ATPase and unwinding activity at different concentrations and time points.